A Comparative Analysis of Competency Expectations between Tourism Professionals and Tourism Academicians - Nagarjuna, G (Atna Journal of Tourism Studies, 2016)
Education is one of the strongest foundations which enable an individual to develop his competency and skills. Education also helps in making positive contributions towards the creation of wealth and quality of life. Educational institutions transform the life of the individual and also makes him contributeto the welfare of the society and organization he or she works for. The organization looks for those candidates who can contribute to the growth and development of the organization through his or her ability and skills. Education institution has to develop skills and abilities among the students which meet the competency expectations of the organization. The purpose of the study is to investigate whether tourism education meets the competency expectation of the tourism industry. The main objective of this study is to find out the gap between competency expectations of tourism academicians and tourism professionals. The scope of the study covers institutions which offer tourism education in Bangalore, Shimoga, and Mangalore. The study also includes service sectors such as travel agencies and tour operators, hotels and airlines within Bangalore. The targeted respondents of the study are tourism faculty members of institutions and tourism professionals in service organizations. Both primary and secondary data are considered to collect the data. Statistical tools such as correlation, paired sample test are used to analyse the data. The study found that there is a gap that exists between perception of academicians and tourism professionals on the benefit of tourism degrees and also insisted more relevant curriculum that meets the needs of the industry. This study also suggested various measures that would help education institutions to meet the expectations of industry by providing skilled workforce.